Evaluation of Surgical Treatment Effect on Idiopathic Normal Pressure Hydrocephalus - Sun, Ran; Ning, Haibo; Ren, Ning; Xing, Xiuying; Chen, Xuejiao; Li, Guihua; Li, Xin; Chen, Lei (Frontiers in Surgery, 2022)
Background: We aimed to observe the long-term effectiveness and safety of the ventriculoperitoneal (VP) shunt in treating idiopathic normal pressure hydrocephalus (iNPH). Methods A total of 65 patients with iNPH were retrospectively analyzed. All the patients were treated with VP shunt and the clinical efficacy was assessed using follow-up questionnaire, the Modified Rankin Scale (mRS), and iNPH grading scale (iNPHGS) after operation. Results The mean mRS and iNPHGS scores were 1.18 ± 0.83 points and 2.98 ± 1.96 points, respectively, which were statistically significantly different from those before operation [(2.89 ± 0.92) points and (6.49 ± 2.30) points, respectively]. Besides, the patients were divided into the non-improvement group (n = 8, 12.3%), the improvement group (n = 16, 24.6%), and the marked improvement group (n = 41, 63.1%) based on the preoperative and postoperative mRS scores and the total effective rate of the VP shunt was 87.7%. Next, seven patients with negative cerebrospinal fluid tap test (tap test) received the active VP shunt and the score on walking disorder was 2.71 ± 0.76 points before operation and 1.86 ± 0.90 points after operation, showing a statistically significant difference. Moreover, 12 (18.4%) patients had complications after operation, among whom 5 (7.7%) patients manifested ameliorated symptoms after replacing shunt tube and receiving anti-infection treatment, but 3 (4.6%) patients showed no alleviation following pressure adjustment due to advanced age and multiple complications. Six (9.2%) cases of death were recorded during follow-up and only 1 (1.5%) case of sudden death occurred within 2 weeks after operation. In addition, it was found through more than 5 years of follow-up after operation that 12 out of the 23 (52.2%) patients had a good effect at 5 years after operation, 1 (4.3%) patient had been confined to bed due to advanced age and pulmonary infection, and 1 (4.3%) patient died of pulmonary infection and heart failure. Conclusion The VP shunt is effective in treating iNPH and it results in a preferable long-term prognosis.